(untitled) (The Review of Diabetic Studies, 2024)
Background: In the recent times, the medical facilities are hiring and retainin nurses, as huge amount of money is being invested in their training and development; then on the other hand at the work level there are a number of restriction for the staffing of nurses, ratio of staffing and even even the use of temporary staff in case of emergencies. A great number of consequences are liable to occur in certain cases of patient care, some of them can be manageable but then again nurses are blamed for the other. This present study will evaluate the scenario in the light of data collected from selected hospitals in Jeddah, Dammam and Riyadh. Study Objectives: The main objective of the study is to find the relationship between nurse staffing levels in terms of ratios and perceived adequacy and patient safety outcomes and self-reported adverse events.. Materials and Methods: Study is based in the hospitals of Dammam, Riyadh and Jeddah city. A sample of 250 nurses was taken for this present study, based on the certain selection or inclusion criteria. Study includes Cross sectional study design and uses Chi Square test as statistical tool. SPSS ver. 27.0 will be used to analyze the data.